Microfinance, rights and global justice - Sorell, Tom, Ed; Cabrera, Luis, Ed (Cambridge University Press, 2015)
Microfinance - the practice of providing small loans to promote entrepreneurial activity among those with few financial assets - is increasingly seen as a sustainable means of aiding the global poor. Perhaps its most influential advocate, Nobel Laureate Muhammad Yunus, has claimed that there is a human right to microfinance, given its potential for poverty alleviation. This book directs critical philosophical attention at this very widely used and praised poverty-reducing measure. In chapters that discuss microfinance schemes and models around the world, internationally renowned contributors address important questions about both the positive impact of microfinance and cases of exploitation and repayment pressure. Exploring how far microfinance can or should be situated within broader concerns about justice, this volume sheds light on ethical issues that have so far received little systematic attention, and it advances discussion on new human rights, exploitation, and global justice.